Perancangan Aplikasi Game “DEFENSE BODY” Sebagai Media Edukasi Kesehatan Untuk Anak-anak - Fairuz Zuyyina; Aileena Solicitor C.R.E.C.; Widyasari (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
Most sources of disease come from dirty items. Dirty items usually have lots of disease-causing bacteria and viruses that can lower our immune system. One of the reasons is unhygienic food. For that, we need interesting and informative educational media in the form of an educational game application "Defense Body". This game aims to educate children about the importance of maintaining health. This design uses a qualitative method with 2 stages carried out, namely the preparation stage and the creation stage. This method approach produces a design concept with the keyword "Learning with fun" as a solution for parents in educating their children about the importance of health. This game is designed as a companion media for parents so that children can understand the importance of maintaining health.